Internal and External Factors Shaping Resilience in Parents of Children with Cerebral Palsy: A Qualitative Study - Asang, Penisa Sampe; Wahyuningrum, Enjang; Kristianingsih, Sri Aryanti (Kuras Institute, 2025)
This study aims to examine the resilience of parents who have children with cerebral palsy and the factors influencing it. A qualitative approach with a case study method was used to explore the subjective experiences of three couples in raising children with special needs. Data were collected through in-depth interviews, participatory observations, and documentation, then analyzed using the Miles & Huberman model, which includes data reduction, data display, and conclusion drawing. The findings show that parental resilience is reflected in their ability to manage emotions, control impulses, maintain optimism, demonstrate empathy, and have self-efficacy. They are also able to perform causal analysis and build meaning in life through the reaching out attitude. Factors influencing resilience are divided into internal and external factors. Internal factors include proactive coping styles, emotional coping, and problem-focused coping, as well as emotional adaptation skills and intelligence in facing challenges. External factors include support from immediate and extended family, social environment, healthcare workers, and spiritual support from religious leaders. This study is expected to provide theoretical contributions in the field of psychology, as well as practical benefits for parents and society in creating adaptive and constructive support for children with cerebral palsy.